Simulation Analysis of the GearModification of Wind Power Gearbox based on Romax - Li Ruiliang; Mu Song; Wang Chunxiu; Su Youliang (Jixie chuandong)
At present,the gearboxes are faced with the problems of high failure rate,large vibration and noise,short service life,etc,and the gear modification is an effective means to reduce vibration and noise,extend life,which is proved by practical experience at home and abroad for many years.With the introduction of some professional gear software or wind turbine analysis software from abroad,the work efficiency is greatly improved,and the extra cost due to experimental verification is also reduced.With the using of RomaxWIND excellent load distribution analysis function and on the basis of the theory of gear modification,the statics simulation analysis of the gearbox is carried out through the RomaxWIND software under the equivalent loads.According to the load distribution on the tooth surface of gear,transmission errors and other parameters,the length,amount and curve of modification of the high-speed gear is determined in the end.The conclusions can provide reference for gear modification.